Afropea: utopie post-occidentale et post-raciste - Miano, Léonora (Bernard Grasset, 2020)
Léonora Miano n'est pas une Afropéenne (afro-européenne). Ceux qui se définissent ainsi ont grandi en Europe.Marquée par l'Afrique subsaharienne, la sensibilité de l'auteur se distingue de celle des Afropéens. Ceux-ci se sont construits en situation de minorité. Ce qui détermine la perception de soi, complique l'identification et la solidarité entre Afropéens et Subsahariens.La France identifie à l'Afrique tous ses citoyens d'ascendance subsaharienne, privilégiant les natifs de ce continent. Cela ne favorise pas l'ancrage des Afropéens dans leur pays, leur capacité à se sentir responsables de son destin.Pourtant, ceux qui se sont donné un nom - Afropéens - dans lequel Afrique et Europe fusionnent, s'ils sont fidèles aux implications de cette association plus qu'à leur amertume, peuvent incarner un projet de société fraternel, anti-impérialiste et anti-raciste. Dans une France en proie aux crispations identitaires, la perspective afropéenne apparaît encore comme une utopie. De part et d'autre, la tentation du rejet est puissante.
Section: 222 pages ; 21 cm
Keywords: afrique; afrique subsaharienne; afro-féminisme; antiracisme; approches et analyses; arts; com5170; cours; discipline; europe; france; féminisme afropéen; féminisme décolonial; histoire et politique; premier cycle; régions géographiques; thématiques; utopie; études littéraires

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Première édition: 1984
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires

Moi, Tituba sorcière –: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Beauchemin, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Section: 223 p., [16] p. de planches : ill. en coul.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires